Practical guide to coproduction in conservation science. Issue 1 (21st November 2022) - Caro, Tim; Andrews, Jeffrey; Clark, Matthew; Borgerhoff Mulder, Monique
Abstract: We considered a series of conservation‐related research projects on the island of Pemba, Tanzania, to reflect on the broad significance of Beier et al.'s recommendations for linking conservation science with practical conservation outcomes. The implementation of just some of their suggestions can advance a successful coproduction of actionable science by small research teams. Key elements include, first, scientists and managers working together in the field to ensure feedback in real time; second, questions jointly identified by managers and researchers to facilitate engaged collaboration; third, conducting research at multiple sites, thereby broadening managers' abilities to reach multiple stakeholders; and fourth, establishing a multidisciplinary team because most of the concerns of local managers require input from multiple disciplines. Resumen: Consideramos una serie de proyectos de investigación relacionados con la conservación en la isla de Pemba, Tanzania, para reflexionar sobre la importancia de las recomendaciones de Beier et al. para vincular las ciencias de la conservación con sus resultados prácticos. La implementación de sólo algunas de sus sugerencias puede impulsar una coproducción exitosa de ciencia práctica hecha por pequeños equipos de investigación. Los elementos clave incluyen, primero, a los científicos y administrados trabajando juntos en el campo para asegurar respuestas en tiempo real; segundo, preguntas identificadas en conjunto por los administradores y los investigadores para facilitar la colaboración participativa; tercero, realizar investigaciones en sitios diferentes y ampliar con esto las habilidades de los administradores para llegar a múltiples actores; y cuarto, establecer un equipo multidisciplinario ya que la mayoría de los intereses de los administradores locales requieren información de múltiples disciplinas. 保护科学中协同生产的实用指南: 【摘要】 本研究分析了坦桑尼亚奔巴岛一系列与保护有关的研究项目, 以思考Beier等(2016)关于将保护科学与实际保护成效联系起来的建议是否具有广泛意义。我们认为, 仅需要实施他们的部分建议就可以推动小型研究团队成功通过协同生产获得可操作的科学成果。其中的关键要素包括:第一, 科学家和管理者进行实地合作来确保实时反馈;第二, 由管理者和研究者共同确定问题, 以促进参与合作;第三, 在多个地点进行研究, 从而扩大管理者与多方利益相关者沟通的能力;第四, 考虑到当地管理者关心的大多数问题都需要多学科投入, 因此应建立一个多学科的团队。【翻译: 胡怡思; 审校: 聂永刚】